Implementasi Lima Pilar Utama dalam Pengabdian Masyarakat Internasional untuk Meningkatkan Pendidikan Anak-Anak Pekerja Migran Indonesia di Malaysia: - - Debora Benedicta Roi; Nenin Astiti Ayunda (Politeknik Piksi Ganesha Indonesia, 2026)
Limited access to formal education and the threat of national identity degradation overshadow the children of Indonesian Migrant Workers (PMI) in Malaysia. This community service aims to describe the implementation of the International Community Service Program